2017
DOI: 10.1101/187732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial Dual-coding Genes inTrypanosomabrucei

Abstract: 13Trypanosoma brucei is transmitted between mammalian hosts by the tsetse fly. In the mammal, they 14 genes may be dual-coding and that RNA editing allows access to both reading frames. We 27 hypothesize that dual-coding genes can protect genetic information by essentially hiding a non-28 selected gene within one that remains under selection. Thus, the complex RNA editing system 29 found in the mitochondria of trypanosomes provides a unique molecular strategy to combat genetic 30 drift in non-selective conditi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 71 publications
0
10
1
Order By: Relevance
“…Small alternative editing events that result in frameshifts, particularly near the 5’ end of the editing domain, would cause the formation of an alternative N‐terminus or else an ORF with an entirely different sequence. These have been identified or inferred in T. brucei (Kirby & Koslowsky, ; Koslowsky et al, ; Madej, Niemann, Hüttenhofer, & Göringer, ; Madina et al, ; Ochsenreiter, Cipriano, & Hajduk, ; Simpson et al, ). The noncanonical L. pyrrhocoris and T. cruzi full length ORF reconstructions with highest support were those in which one or a few alternative editing events in a discrete region shift the reading frame such that the encoded protein contains a canonical central domain with an altered N‐ or C‐terminus (Gerasimov et al, ).…”
Section: Knowledge Gained From High Throughput Sequencing Methodologiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Small alternative editing events that result in frameshifts, particularly near the 5’ end of the editing domain, would cause the formation of an alternative N‐terminus or else an ORF with an entirely different sequence. These have been identified or inferred in T. brucei (Kirby & Koslowsky, ; Koslowsky et al, ; Madej, Niemann, Hüttenhofer, & Göringer, ; Madina et al, ; Ochsenreiter, Cipriano, & Hajduk, ; Simpson et al, ). The noncanonical L. pyrrhocoris and T. cruzi full length ORF reconstructions with highest support were those in which one or a few alternative editing events in a discrete region shift the reading frame such that the encoded protein contains a canonical central domain with an altered N‐ or C‐terminus (Gerasimov et al, ).…”
Section: Knowledge Gained From High Throughput Sequencing Methodologiesmentioning
confidence: 94%
“…Evidence that noncanonical editing generates alternative ORFs, as shown in the middle panel in Figure , has been extensively sought with some success. Alternatively edited mRNA molecules or reconstructed ORFs have been identified in T. brucei , T. cruzi , L. mexicana , L. pyrrhocoris , and Perkinsela (Gerasimov et al, ; Kirby & Koslowsky, ; Madina et al, ; Maslov, ; Ochsenreiter & Hajduk, ; Read et al, ; Read, Wilson, et al, ; Simpson et al, ). The more targeted studies have also identified the gRNAs that could direct these alternative editing events (Kirby & Koslowsky, ; Madina et al, ; Ochsenreiter & Hajduk, ).…”
Section: Knowledge Gained From High Throughput Sequencing Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations